(untitled) (Lead City International Journal of Library, Information & Communication Sciences, 2024)
The need to increase library use through effective service quality may be achieved through examining the interplay of emotional intelligence and service quality in libraries. It is against this backdrop that this study investigates the influence of emotional intelligence on service quality, especially in colleges of agriculture in Oyo State, Nigeria. The survey design of the correlational type was adopted. The population of this study was library personnel (27) and Higher National Diploma students (1,846) in colleges of agriculture in Oyo State. Total enumeration was used for the library personnel while 10% proportional sample size was used for the student (185). Questionnaire was the instrument used. The data were analyzed using descriptive statistics, Pearson product moment correlation and Multiple regression at 0.05 level of significance. The study found highly positive perspectives of levels of service quality =2.4) among the indicators. There is high level of emotional intelligence of library personnel in colleges of agriculture in Oyo State, Nigeria and the prominent was Self-awareness (=3.4). The study however found that emotional intelligence (r=.028) demonstrated no significant impact on library service quality. It was concluded that library services in education requires some level of emotional intelligence even when this is not obvious to those concerned. Thus, the institution and library management should develop interventions to empower library personnel toward mastering self-awareness to enhance library service quality.